Advanced characterization and in-situ growth monitoring of Cu(In, Ga)Se2 thin films and solar cells. (August 2018) - Abou-Ras, D.; Bär, M.; Caballero, R.; Gunder, R.; Hages, C.; Heinemann, M.D.; Kaufmann, C.A.; Krause, M.; Levcenko, S.; Mainz, R.; Márquez, J.; Nikolaeva, A.; et al.
Highlights: Overview of advanced characterization work at Helmholtz-Zentrum Berlin. In-situ monitoring of Cu(In, Ga)Se2 growth via X-ray diffraction and light scattering. Structural characterization and analyses of surfaces and interfaces. Microscopic studies of structure–property relationships of Cu(In, Ga)Se2 thin films. Optical analysis via luminescence spectroscopy. Abstract: The continuous improvement of Cu(In, Ga)Se2 (CIGSe) solar cells relies considerably on advanced characterization of individual layers in the solar-cell stacks as well as of completed CIGSe devices. The present contribution provides an overview of corresponding efforts performed by various research groups at Helmholtz-Zentrum Berlin für Materialien und Energie GmbH. In-situ growth monitoring of CIGSe absorber layers by means of energy-dispersive X-ray spectrometry and light scattering is described, as well as structural analyses by means of X-ray and neutron diffraction. In addition, the characterization of surfaces and interfaces by soft X-ray and electron spectroscopy, the microscopic analysis by means of correlative electron microscopy, and optoelectronic characterization by optical spectroscopy are highlighted. The present contribution shows which substantial efforts in a research network are necessary in order to obtain deeper insight into materials properties and potentially limiting factors for the device performance, as well as to be able to control these factors during the solar-cell production.